IMPACT OF INSTAGRAM ADVERTISEMENTS IN INCREASING THE CUSTOMER EXPENSES - Prasad, Ramya K; V, Harini; L, Ramya (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Instagram is a social media platform which most of the youngsters use. This platform is one of the most widely used ones. Instagram gives advertisements to its users based on the algorithm of what they search in various other applications like Amazon, Flipkart, Google, Myntra, Meesho, Ajio, …etc… The advertisements are very frequently displayed, in most cases like after every two posts/stories/reels. This gives the users an increased exposure to the advertisements and it has some kind of impact on their expenditure pattern, which the researcher intends to study in this research paper. The main objective of this study is to ascertain the impact of Instagram advertisements in increasing the purchase of products advertised among its audience, thereby increasing the customer expenses. The researchers have used Social Media Impact Theory, Technological Determinism Theory, Two Step Flow Theory, Selective Influences Theory and Uses and Gratification Theory as the theoretical framework. The study finds that the expenditure of the customers is increasing due to the unintentional purchase made because of the influence of Instagram advertisements and the factors were tested using chi-square association to prove the hypotheses.